2020
DOI: 10.3390/ijms21124565
|View full text |Cite
|
Sign up to set email alerts
|

Newly Identified Regulators of Ovarian Folliculogenesis and Ovulation

Abstract: Each follicle represents the basic functional unit of the ovary. From its very initial stage of development, the follicle consists of an oocyte surrounded by somatic cells. The oocyte grows and matures to become fertilizable and the somatic cells proliferate and differentiate into the major suppliers of steroid sex hormones as well as generators of other local regulators. The process by which a follicle forms, proceeds through several growing stages, develops to eventually release the mature oocyte, and turns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 123 publications
(150 reference statements)
0
77
0
Order By: Relevance
“…These phenomena suggested that PCOS may be a chronic low-grade inflammatory disease (5). The low-grade chronic inflammation in PCOS patients is mainly attributed to accumulated visceral fat (2,4), in which adipocytes undergo necrosis after hypoxia and gather many inflammatory cells to produce numerous inflammatory cytokines (6,7). Therefore, chronic low-grade inflammation plays an irreplaceable role in PCOS progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena suggested that PCOS may be a chronic low-grade inflammatory disease (5). The low-grade chronic inflammation in PCOS patients is mainly attributed to accumulated visceral fat (2,4), in which adipocytes undergo necrosis after hypoxia and gather many inflammatory cells to produce numerous inflammatory cytokines (6,7). Therefore, chronic low-grade inflammation plays an irreplaceable role in PCOS progression.…”
Section: Introductionmentioning
confidence: 99%
“…The follicle is the basic functional unit of oocyte generation and development, it induces human germ cell maturation and ovulation (7,8). GCs control meiosis in mammalian follicles before ovulation (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The Hippo pathway is critical in folliculogenesis and ovarian function by regulating follicle activation and survival, and ovarian cells proliferation (21). The key molecules of the Hippo pathway, including Large tumor suppressor 1/2 (LATS1/2), Mammalian Ste20-like kinases 1/2 (MST1/2), Yes-associated protein (YAP), PDZ-binding motif (TAZ), and TEA domain transcription factor (TEAD), play a critical regulatory function in the cytoplasm of GCs (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that decreased levels of Cyp11a1 or Cyp19a1 disrupt the development of antral and Graafian follicles (Gershon and Dekel, 2020). The reduced level of Gata4 expression in Erβ null GCs may contribute to reduced GC proliferation and theca cell recruitment, which would impair the maturation of follicles to the preovulatory stage (Bennett et al, 2013;Efimenko et al, 2013;LaVoie, 2014).…”
Section: Discussionmentioning
confidence: 99%